Strategy, Discourse and Practice: The Intensification of Power. (7th January 2013) - Hardy, Cynthia; Thomas, Robyn
Abstract We adopt a Foucauldian approach to discourse to show how power relations shape the constitution of strategy. By exploring two particular discourses associated with the strategy of a global telecommunications company, our study shows how the power effects of discourses are intensified through particular discursive and material practices, leading to the production of objects and subjects that are clearly aligned with the strategy. In this way, our study contributes to understanding: the mechanisms whereby discourse bears down on strategy through intensification practices; different forms of resistance; and the way in which strategy objects and subjects reproduce (or undermine) discourse.